SIFAT VENIR DAN KAYU LAPIS ENAM JENIS KAYU UNTUK HUTAN TANAMAN INDUSTRI - Rodjak Memed; M I Iskandar; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
The characteristics studied are peeling  properties, physical properties of  the  veneer,  gluing  properties  and  some physical   and  mechanical  properties of  the  plywood  (both   triplex and  multiplex).